Insufficient nitrogen supply from symbiotic fixation reduces seasonal crop growth and nitrogen mobilization to seed in highly productive soybean crops - Cafaro la Menza, Nicolás (2020)
Nitrogen (N) supply can limit the yields of soybean [Glycine max (L.) Merr.] in highly productive environments. To explore the physiological mechanisms underlying this limitation, seasonal changes in N dynamics, aboveground dry matter (ADM) accumulation, leaf area index (LAI) and fraction of absorbed radiation (fAPAR) were compared in crops relying only on biological N2 fixation and available soil N (zero-N treatment) versus crops receiving N fertilizer (full-N treatment). Experiments were conducted in seven high-yield environments without water limitation, where crops received optimal management. In the zero-N treatment, biological N2 fixation was not sufficient to meet the N demand of the growing crop from early in the season up to beginning of seed filling. As a result, crop LAI, growth, N accumulation, radiation-use efficiency and fAPAR were consistently higher in the full-N than in the zero-N treatment, leading to improved seed set and yield. Similarly, plants in the full-N treatment had heavier seeds with higher N concentration because of greater N mobilization from vegetative organs to seeds. Future yield gains in high-yield soybean production systems will require an increase in biological N2 fixation, greater supply of N from soil or fertilizer, or alleviation of the trade-off between these two sources of N in order to meet the plant demand.